Oxygen diffusion through perovskite membranes - Wang, Haihui; Yang, Weishen; Tablet, Cristina; Caro, Jürgen (Diffusion Fundamentals, 2005)
The oxygen permeation flux through the perovskite membrane made of Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) has been measured as a function of both the temperature and the oxygen pressure gradient across the membrane. A simple model for the surface exchange fluxes was used to understand the mechanism of the oxygen transport. The limiting step of the oxygen transport was found to be the bulk diffusion for the BSCF perovskite at temperatures above 700 oC. Furthermore, the oxygen vacancy diffusion coefficient (Dv) can be deduced from the dependence of the oxygen permeation flux on the oxygen pressure gradient. From permeation measurement on the BSCF membrane tube, Dv is between 2.82×10-9 m2/s at 900 oC and 0.82×10-9 m2/s at 700 oC.